Mini-review of interesting properties in Mn2CoAl bulk and films - Yang, Ying (Frontiers in Chemistry, 2022)
Heusler compounds exhibit many interesting properties, such as high thermopower, magnetocaloric properties, and even topological insulator states. Heusler Mn2CoAl alloy has been experimentally and theoretically proposed as a promising spin-gapless semiconductor with novel electronic, magnetic, spintronic, transport, and topological properties. Furthermore, the spin-gapless semiconducting-like behaviors are also predicted in Mn2CoAl films by measuring the transport and magnetic properties. This mini-review systematically summarizes the interesting properties of Mn2CoAl bulk and Mn2CoAl-based films. This mini-review is hoped to guide further experimental investigations and applications in the particular scientific community.